PRECISE FORMULA FOR VOLUME COMPUTATIONS USING CONTOURS METHOD - Napoles, E.; Berber, M. (Boletim de Ciências Geodésicas, 2018)
Except some special cases, commonly used volume computation methods are grids method, contours method and volume computations by utilizing TIN (Triangulated Irregular Network). In this study, to investigate the precisions of these techniques, a grid system is established in an undulating area and volume of the mound is determined by using these three volume computation methods. It is found out that contour method results were not as price as the other two methods. Thus, a precise formula for volume computations using contours method is proposed.